Political Economic Dilemma of Member States of the Southern African Development Community (SADC) - Putra, Gilang Rizki Aji; Yunus, Nur Rohim; Abdurofiq, Atep (BULETIN ADALAH, 2023)
This article examines the political economy dilemmas facing member states of the Southern African Development Community (SADC). SADC is a regional organization that aims to promote economic cooperation among countries in the region. However, despite the enormous potential for economic integration and development, SADC members often face complex political economic challenges. This article explores the internal and external factors influencing economic and political policies in SADC countries, as well as their impact on regionalism and development efforts.